Treatment of Cystic Fibrosis: From Gene- to Cell-Based Therapies - Allan, Katelin M.; Farrow, Nigel; Donnelley, Martin; Jaffe, Adam; Waters, Shafagh A. (Frontiers in Pharmacology, 2021)
Prognosis of patients with cystic fibrosis (CF) varies extensively despite recent advances in targeted therapies that improve CF transmembrane conductance regulator (CFTR) function. Despite being a multi-organ disease, extensive lung tissue destruction remains the major cause of morbidity and mortality. Progress towards a curative treatment strategy that implements a CFTR gene addition-technology to the patients’ lungs has been slow and not yet developed beyond clinical trials. Improved delivery vectors are needed to overcome the body’s defense system and ensure an efficient and consistent clinical response before gene therapy is suitable for clinical care. Cell-based therapy–which relies on functional modification of allogenic or autologous cells ex vivo, prior to transplantation into the patient–is now a therapeutic reality for various diseases. For CF, pioneering research has demonstrated proof-of-principle for allogenic transplantation of cultured human airway stem cells into mouse airways. However, applying a cell-based therapy to the human airways has distinct challenges. We review CF gene therapies using viral and non-viral delivery strategies and discuss current advances towards autologous cell-based therapies. Progress towards identification, correction, and expansion of a suitable regenerative cell, as well as refinement of pre-cell transplant lung conditioning protocols is discussed.